Personality traits as predictors of desirable organizational culture - Radovanović, Dragana; Okanović, Predrag (Primenjena psihologija, 2009)
The main aim of this research is to establish whether personality traits can be predictors of desirable organizational culture, and, if so, which traits are related to particular factors of organizational culture. The research was conducted on a sample of 294 participants (94 males and 200 females). The sample comprised the senior students and graduates of the University of Novi Sad. Two instruments were employed : the Big Five Inventory (BFI) and a revised questionnaire for organizational culture assessment – Organizational Culture Profile. The latter measures seven factors: Competitiveness, Social Responsibility, Supportiveness, Innovation, Stability, Emphasis on Rewards and Performance Orientation. A two – way multivariate analysis of covariance was performed. Gender and the field of study were categorical predictors, the continuous predictors were the BFI scores, and the criteria were the scores on the seven organizational culture factors. The significant predictors of the desirable organizational culture were Agreeableness and Openness, while none of the categorical predictors was significant.